Public sector entities in the financial statements relative analysis: theoretical and practical aspects - Jusytė, Jovita; Kamarauskienė, Irma (Buhalterinės apskaitos teorija ir praktika, 2014)
In the current stage of economic globalisation and development public sector finances is a factor that to a large extent influences the national economic development. There is an express need on the part of users of financial information not only to understand the accounting information pertaining to public sector entities (hereinafter – PSE), but also to be able to compare the data of the different entities within the sector, compare and evaluate reports on financial standing of PSEs of different countries. There emerged a tangible need to standardise the accounting information or the data on the used budget appropriations irrespective of the user’s national language, or his education, or any other subjective factors – it became important to ensure that the principal information is understandable irrespective of the national language, financial literacy or other subjective factors of the user of the information. The accounting reform than launched and still in progress is only part of the comprehensive reform of accounting in the public sector that is currently under implementation both in the European Union, Economic Community, as well as other economically developed States. The article aims to explore the possibility of public-sector entities in the financial statements prepared on an accrual basis of data analysis for profit-making enterprises of the financial statements used in the analysis of relative performance. The presented theoretical and practical aspects and proposed new indicators, announced study carried out.